Relationship Between Appropriateness of Empirical Antibiotics Based on ATS/IDSA with Clinical Outcome and Length of Stay in ICU (Intensive Care Unit) Patient with Sepsis Pneumonia - Muhammad Luthfi Aziz; Ika Puspita Sari; Rizka Humardewayanti Asdie (Universitas Islam Indonesia, 2022)
Background: In ICU (Intensive Care Unit), sepsis is the most common cause of death, with pneumonia being the most common source of infection. The management of sepsis pneumonia is determined by the therapy used. One of the supporting aspects in the successful treatment of sepsis pneumonia is appropriate empiric antibiotic therapy.Objective: Determine the relationship between the appropriateness of empirical antibiotics based on ATS/IDSA (American Thoracic Society/ The Infectious Disease Society of America) with clinical outcome and LOS (Length Of Stay) in ICU patients with sepsis pneumonia.Method: An observational study with a retrospective cohort design in ICU patients with sepsis pneumonia from January 2019-December 2020 at RS X Jakarta. The study involved 99 patients who were divided into two groups based on appropriate and inappropriate with ATS/IDSA. Data were analyzed using bivariate and multivariate for reducing the confounding factor.Results: The appropriateness of empirical antibiotics was found to be appropriate in 48.48% (48 patients), while 51.52% (51 patients) were inappropriate with ATS/IDSA. There was a relationship between empirical antibiotic appropriateness and clinical outcome (p=0.042; RR=1.430; 95%CI=1.039-1.969) based on the chi-square test, but no relationship with LOS (p=0.629) based on the Mann Whitney test. The multivariate analysis showed that there were no confounding factors affecting the clinical outcome (p>0.05).Conclusion: There is a relationship between empirical antibiotic appropriateness based on ATS/IDSA with clinical outcomes but not related to the length of stay in sepsis pneumonia patients in the ICU.Keywords: sepsis pneumonia, antibiotic empiric, clinical outcome, LOS IntisariLatar belakang: Sepsis merupakan penyebab kematian terbanyak di ICU (Intensive Care Unit), dengan sumber infeksi tertinggi adalah pneumonia. Keberhasilan pengobatan sepsis pneumonia bergantung pada terapi yang diberikan. Pemberian terapi antibiotik empirik yang sesuai merupakan salah satu faktor penunjang keberhasilan pengobatan sepsis pneumonia.Tujuan: Mengetahui hubungan kesesuaian antibiotik empirik berdasarkan ATS/IDSA (American Thoracic Society/ The Infectious Disease Society of America) dengan outcome klinik dan lama waktu rawat pasien sepsis pneumonia di ICU.Metode: Penelitian observasional dengan rancangan kohort retrospektif pada pasien ICU dengan diagnosis sepsis pneumonia periode 1 Januari 2019-31 Desember 2020 di RS X Jakarta. Penelitian melibatkan 99 pasien yang terbagi dalam kelompok sesuai dan tidak sesuai ATS/IDSA. Data dianalisis dengan uji bivariat serta multivariat untuk mereduksi variabel pengganggu.Hasil: Kesesuaian antibiotik empirik diperoleh sebesar 48,48% (48 pasien) telah sesuai dan 51,52% (51 pasien) tidak sesuai ATS/IDSA. Berdasarkan hasil uji chi-square terdapat hubungan kesesuaian antibiotik empirik dengan outcome klinik (p=0,042; RR=1,430; 95%CI=1,039-1,969) dan berdasarkan uji mann whitney tidak terdapat hubungan antara kesesuaian antibiotik empirik dengan lama waktu rawat (p=0,629). Hasil analisis multivariat menunjukkan tidak ada faktor pengganggu yang mempengaruhi outcome klinik (p>0,05).Kesimpulan: Kesesuaian antibiotik empirik berdasarkan ATS/IDSA pada pasien sepsis pneumonia di ICU memiliki hubungan dengan outcome klinik namun tidak berhubungan dengan lama waktu rawat.Kata kunci: sepsis pneumonia, antibiotik empirik, outcome klinik, lama waktu rawat